(untitled) (Tribhuvan University Journal of Microbiology, 2019)
Objectives: The main objective of this study was to determine the prevalence of Escherichia coli among urinary tract infection (UTI) suspected patients visiting tertiary care hospital and to assess the biofilm producing ability of E. coli isolates. Methods: A prospective cross-sectional study was carried out in Biratnagar Metropolitan city, Eastern Nepal from December 2018 to May 2019. During the study 400 urine samples were collected from UTI suspected patients visiting a tertiary care hospital of Biratnagar. Urine samples were cultured by using semi-quantitative culture technique and identified. Antibiotic susceptibility testing was done by Kirby-Bauer Disk Diffusion method according to CLSI (2011) guidelines. Biofilm assays were performed by microtitre plate method. Results: This study reported 15% prevalence of E. coli out of 400 urine samples. 100% of E. coli isolates showed resistance to both Ampicillin and Amoxicillin while 100% were sensitive to Chloramphenicol. 70% (42/60) isolates were Multi Drug Resistance (MDR)E. coli. The maximum isolates (86.66%) were found to be biofilm producers by microtitre plate method. Resistance to other antibiotics such as Nalidixic acid (71.11% vs 46.66%), Norfloxacin (53.33% vs 46.66%), Cotrimoxazole (42.22% vs 26.66%) was comparatively higher among biofilm producers than non-biofilm producers. There was a significance of association between biofilm and MDR (p<0.05). Conclusion: There is relation between the ability of biofilm formation and drug resistance in the bacterium resulting to the failure of antibacterial drugs.